A new approach to laser DED as a repair technology with laser mesh deposition - Thomas Girerd; Richard Adamson; Andres Gameros; Marco Simonelli; Andy Norton; Adam Thomas Clare (Additive Manufacturing Letters)
Controlling the heat input and exploring alternate feedstocks for DED is necessary to improve the versatility of DED as a repair technique. In this research, a new DED method using metallic mesh feedstocks and laser beam oscillations. This method is shown to have good stability, repeatability and good bonding with the substrate comparable to other DED processes. The best depositions show a dilution above 40 % and a height of >1.2 mm. The deposits show similar results to wire DED and powder DED with low dilution levels producing dense clads with no large pores and some grain refinements at the edges of the tracks. This then manifests as a potentially viable repair process with the advantage of a more flexible material input facilitating the delivering of the feedstock material for hard to access repair operations.Furthermore, this process has shown its capability to be used with various energy profiles and mesh density paving the way for a better control of the microstructure for complex repair operations. This new DED alternative method has shown its capability to run efficiently with various scan strategies and feedstocks. Hence, laser mesh deposition could be used to deposit material on inhomogeneous surfaces by using carefully designed scanning strategies and mesh density during the process increasing the repair capabilities of DED.